2003
DOI: 10.1103/physreve.68.036103
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic processes with immunization

Abstract: We study a model of directed percolation (DP) with immunization, i.e. with different probabilities for the first infection and subsequent infections. The immunization effect leads to an additional nonMarkovian term in the corresponding field theoretical action. We consider immunization as a small perturbation around the DP fixed point in d < 6, where the non-Markovian term is relevant. The immunization causes the system to be driven away from the neighbourhood of the DP critical point. In order to investigate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 41 publications
4
36
0
Order By: Relevance
“…The occurrence of percolation is a geometric phase transition of the network structure that has a profound impact on network dynamics and function. Percolation theory has been successfully applied to investigate various phenomena in nature such as the spread of forest fires [3], the transmission and extinction of infectious diseases and the impact of immunization [4,5], the emergence of life [6], and the formation of a city [7], to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of percolation is a geometric phase transition of the network structure that has a profound impact on network dynamics and function. Percolation theory has been successfully applied to investigate various phenomena in nature such as the spread of forest fires [3], the transmission and extinction of infectious diseases and the impact of immunization [4,5], the emergence of life [6], and the formation of a city [7], to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…12 Epidemic processes with immunization are also considered recently in relation to direct percolation. 13 A further approach using the relation to percolation is proposed in. 14 Here, we use the SIR-model in its simplest form; a node takes on one of three states, S, I, R, where for computer networks, the R-state represents recovered with the virus removed and anti-virus software is installed.…”
Section: Modelmentioning
confidence: 99%
“…A more interesting way of accounting for memory effects is by letting the jump probability to a given site be ∼ exp(ku), where k = 1 for sites already visited at least once and k = 0 for the others. This model, called the one-step (true) reinforced random walk, is related to the Donsker-Varadhan Wiener sausage problem [13][14][15], and its properties have been studied in detail in [12,[16][17][18][19]. In particular, it was shown that in high-dimensional lattices (d 2) it exhibits a nontrivial phase transition between a diffusive and a collapsed phase as a function of the parameter u.…”
Section: Introductionmentioning
confidence: 99%